Computer, intelligent computing and education technology. selected peer reviewed papers from 2014 International Conference on Computer Intelligent Computing and Education, CICET 2014, Hongkong, 27-28 March 2014 /: selected peer reviewed papers from 2014 International Conference on Computer Intelligent Computing and Education, CICET 2014, Hongkong, 27-28 March 2014. Volume 1 : (2014) - Unknown
No abstract available